(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Twenty mixed breed rabbit bucks aged between 6–8 weeks with an average weight of 861g were randomly assigned to four (4) dietary treatments with five (5) bucks per treatment in a Completely Randomized Design to determine the effect of feeding graded levels of Vitamin E on sperm morphology and semen characteristics of rabbit bucks. The rabbits received graded levels of vitamin E/kg feed (0mg/kg, 20 mg/kg, 40 mg/kg and 60 mg/kg for treatments 1, 2, 3 and 4, respectively). Feed and water were given to the rabbit bucks ad libitum during the experiment. The semen collected was taken to laboratory for sperm morphology and semen characteristics and the data collected were analysed using general linear model procedure of statistical analysis system (SAS). The results revealed that the mean number of normal cells, detached head and mid piece defect were not significantly (P>0.05) different across the treatments. However, the percent abnormal defects percent of free tail and coiled tail were significantly (P<0.05) lower for rabbits fed 20 and 60 mg/kg and the least bent tail was obtained in 60 mg/kg diet. The results for semen characteristics had significant (P<0.05) differences in all the parameters except for semen volume and pH. The results showed that those fed 60 mg/kg of vitamin E diet gave significantly (P<0.05) higher sperm motility, sperm concentration, live ratio and low dead ratio (87.50 %, 232x106, 87.50 % and 12.00 %) respectively. Therefore, supplementation of vitamin E at 60mg/kg in the diet of rabbit bucks is recommended